Patient perspectives on low back pain treatment in primary care: a qualitative study of hopes, expectations, and experiences - Simon Dyrløv Madsen; Mette Jensen Stochkendahl; Lars Morsø; Merethe Kirstine Andersen; Elisabeth Assing Hvidt (BMC Musculoskeletal Disorders)
Abstract Background Patients’ hopes and expectations for low back pain treatment influence their consultation experiences and treatment outcomes. These hopes and expectations may evolve over time, potentially leading to a shift in what patients consider important before and after a consultation. Understanding the distinction between hopes and expectations, and how they evolve is important for improving patient care. This study explored patients’ hopes and expectations prior to LBP consultations and examined how these were reflected in their post-consultation experiences. Methods We employed a qualitative design consisting of individual semi-structured pre- and post-consultation interviews with patients seeking care for low back pain from general practitioners, physiotherapists, and chiropractors in Denmark. A convenience sample of 18 patients (10 females and 8 males) aged between 28 and 79 years were interviewed about their hopes and expectations before a consultation and their experiences immediately following the consultation. Data were analysed employing Braun and Clarke’s thematic analysis. Results Two themes with five subthemes were developed: (1) “Something needs to be done,” which included subthemes related to life disruption, expectations of clinical assessment, and the clinicians as experts; and (2) “Experiences and emotional responses to the interaction with the clinician”, highlighting the importance of trust and the personal attributes of clinicians. Patients initially sought urgent help and clarity regarding their condition but shifted their focus post-consultation to the relational dynamics and emotional engagement experienced during interactions with clinicians. Conclusions This study contributes to the understanding of how patients’ hopes and expectations regarding low back pain consultations evolve, shifting from a focus on clinical actions and outcomes to valuing interpersonal relationships and emotional support from clinicians. Recognising these shifts can enhance clinician-patient interactions and improve overall patient satisfaction and treatment outcomes. Clinical trial number Not applicable.